2023
DOI: 10.1158/0008-5472.can-23-0705
|View full text |Cite
|
Sign up to set email alerts
|

Abemaciclib Is Effective in Palbociclib-Resistant Hormone Receptor–Positive Metastatic Breast Cancers

Abstract: Cyclin-dependent-kinase-4/6 inhibitor (CDK4/6i) plus endocrine therapy (ET) is standard of care for patients with hormone receptor (HR)-positive, HER2-negative metastatic breast cancer (MBC). However, resistance to CDK4/6is plus ET remains a clinical problem with limited therapeutic options following disease progression. Different CDK4/6is might have distinct mechanisms of resistance, and therefore using them sequentially or targeting their differentially altered pathways could delay disease progression. To un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 84 publications
2
4
0
Order By: Relevance
“…However, We did not observe sequential abemaciclib obtained longer PFS compared to nonsequential abemaciclib (6.0 vs. 6.0 months) though patients received fewer lines of prior systemic therapy and had longer PFS from prior palbociclib in the sequential arm compared to the nonsequential arm, in line with the study by Navarro‐Yepes et al (6.2 vs. 6.1 months), 45 contrary to the retrospective study by Wander et al, (8.4 vs. 3.0 months, p = 0.0013) 47 . Interestingly, Navarro‐Yepes et al found sequential abemaciclib obtained significantly longer median OS for patients treated sequentially (42.7 months vs.17.3 months) 45 . Real‐world data from the Flatiron Health Network showed that continuation of CDK4/6 inhibitor after progression on first‐line CDK4/6 inhibitor was significantly associated with improved PFS and OS 48 .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…However, We did not observe sequential abemaciclib obtained longer PFS compared to nonsequential abemaciclib (6.0 vs. 6.0 months) though patients received fewer lines of prior systemic therapy and had longer PFS from prior palbociclib in the sequential arm compared to the nonsequential arm, in line with the study by Navarro‐Yepes et al (6.2 vs. 6.1 months), 45 contrary to the retrospective study by Wander et al, (8.4 vs. 3.0 months, p = 0.0013) 47 . Interestingly, Navarro‐Yepes et al found sequential abemaciclib obtained significantly longer median OS for patients treated sequentially (42.7 months vs.17.3 months) 45 . Real‐world data from the Flatiron Health Network showed that continuation of CDK4/6 inhibitor after progression on first‐line CDK4/6 inhibitor was significantly associated with improved PFS and OS 48 .…”
Section: Discussionsupporting
confidence: 90%
“…Importantly, this study found palbociclib‐resistant cells upregulated G2‐M pathways and abemaciclib could mediate G2 arrest of palbociclib‐resistant cells. Furthermore, these findings were confirmed by both patient‐derived xenografts (PDX) and PDX‐derived organoids models of palbociclib‐resistant BC 45 . Overall, these promising results indicate that the use of abemaciclib plus different ET after progression on prior palbociclib might be a feasible treatment strategy in addition to chemotherapy.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“… 72 , 73 , 74 For instance, nonluminal subtypes within the HR+/HER2– disease have been associated with a poorer response to endocrine therapy, 75 , 76 while different transcriptomic profiles have been reported among cells resistant to different CdK4/6 inhibitors, which could have relevant clinical implications. 77 Therefore transcriptomics represents a powerful tool to understand the phenotypical characteristics of BC and to guide treatment choices. Intrinsic subtypes are now being used as inclusion criteria in several prospective trials (e.g.…”
Section: Beyond Genomics Assessing New Dimensions Of Cancer Biologymentioning
confidence: 99%